Chueta population: Diversity and forensic parameters of a small, isolated and endogamic population. Issue 1 (December 2019) - Ferragut, J.F.; Castro, J.A.; Ramon, C.; Picornell, A.
Abstract: Chuetas are the descendants of the condemned Crypto-Jews in the last Inquisition processes in Majorca (Balearic Islands, Spain). Despite their conversion, they were discriminated against and secluded by their immediate neighbours. Due to their isolation Chuetas' genetic diversity was expected to be considerably low. Contrary to this, diversity found in most of the markers studied show that the diversity in this population is as high as in other Jewish or islander populations studied to date. Only in haploid markers, discrimination capacity is significantly low.